2021
DOI: 10.1002/mus.27466
|View full text |Cite
|
Sign up to set email alerts
|

Laryngospasm in amyotrophic lateral sclerosis

Abstract: Introduction: Laryngospasm is an involuntary, sustained closure of sphincter musculature that leads to an unpleasant subjective experience of dyspnea and choking. It is an underreported symptom in amyotrophic lateral sclerosis (ALS). In this study we aimed to better characterize the prevalence and clinical characteristics of laryngospasm in ALS patients. Methods:The medical records of 571 patients with ALS followed between 2008 and 2018 were searched for evidence of laryngospasm. A total of 23 patients with la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Contrary to prior data on laryngospasm in patients with SBMA 6 or other neurologic conditions, 2 the authors found that smoking and gastroesophageal reflux disease (GERD) were not major risk factors in patients with ALS. Instead, aspirating secretions was the most common trigger in the present study, reported in more than a third of patients, a frequency more than double that of the next most common trigger 1 . This suggests that sialorrhea, or more precisely pseudo‐sialorrhea due to bulbar dysfunction, is one major risk factor predisposing to vocal cord irritation and laryngospasm in patients with ALS.…”
Section: Triggers and Approaches To Treatmentmentioning
confidence: 46%
See 3 more Smart Citations
“…Contrary to prior data on laryngospasm in patients with SBMA 6 or other neurologic conditions, 2 the authors found that smoking and gastroesophageal reflux disease (GERD) were not major risk factors in patients with ALS. Instead, aspirating secretions was the most common trigger in the present study, reported in more than a third of patients, a frequency more than double that of the next most common trigger 1 . This suggests that sialorrhea, or more precisely pseudo‐sialorrhea due to bulbar dysfunction, is one major risk factor predisposing to vocal cord irritation and laryngospasm in patients with ALS.…”
Section: Triggers and Approaches To Treatmentmentioning
confidence: 46%
“…The authors report that their patients' most commonly used therapies for laryngospasm were relatively ineffective, with most showing benefit in less than 10% of patients. 1 The lack of effective treatments, as perceived by those affected, may indicate lack of understanding on the part of patients about the triggers discussed above, and consequently uncertainty of the cause of their laryngospasm and how to prevent or mitigate it. This highlights an important need for education and for shared decision-making about symptom management, especially because laryngospasms were occasionally frequent and severe.…”
Section: Triggers and Approaches To Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Laryngospasm is distinct from induced laryngeal obstruction (ILO), a recently proposed disease concept that causes relatively mild breathing problems mainly on exertion 8) . The causes of laryngospasm may include endotracheal maneuvers, reflux esophagitis, amyotrophic lateral sclerosis, and hypomagnesemia [9][10][11] . Idiopathic cases of recurrent laryngospasm with no apparent cause have also been reported 12,13) .…”
Section: Discussionmentioning
confidence: 99%